2022
DOI: 10.1177/08968608221096556
|View full text |Cite
|
Sign up to set email alerts
|

The rationale for the need to study sodium-glucose co-transport 2 inhibitor usage in peritoneal dialysis patients

Abstract: The wave of kidney and heart outcome trials, showing multiple potential benefits for sodium-glucose co-transport 2 (SGLT2) inhibitors, have excluded patients with an estimated glomerular filtration rate below 25 ml/min/1.73 m2. However, dialysis patients are at the highest risk of cardiovascular disease and would benefit most from effective cardioprotective therapies. There is emerging evidence from experimental studies and post hoc analyses of randomised clinical trials that SGLT2 inhibitors are well tolerate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…There is growing evidence of SGLT2 inhibitor's role in the prevention of cardiovascular mortality and kidney function deterioration which may be of particular benefit in patients on dialysis. 9 Reports suggest that mechanisms other than simple paracellular diffusion are involved in glucose leakage during PD, namely SGLTs and glucose transporters (GLUTs) responsible for transcellular transport via mesothelial cells. 10,11 Schroppel et al found that SGLT1 is located on the apical surface of peritoneal mesothelial cells, while GLUTs -on the basolateral surface of these cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is growing evidence of SGLT2 inhibitor's role in the prevention of cardiovascular mortality and kidney function deterioration which may be of particular benefit in patients on dialysis. 9 Reports suggest that mechanisms other than simple paracellular diffusion are involved in glucose leakage during PD, namely SGLTs and glucose transporters (GLUTs) responsible for transcellular transport via mesothelial cells. 10,11 Schroppel et al found that SGLT1 is located on the apical surface of peritoneal mesothelial cells, while GLUTs -on the basolateral surface of these cells.…”
Section: Introductionmentioning
confidence: 99%
“…There is growing evidence of SGLT2 inhibitor’s role in the prevention of cardiovascular mortality and kidney function deterioration which may be of particular benefit in patients on dialysis. 9…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13] Borkum et al subsequently discuss the importance of studying SGLT2 inhibition as a therapy to preserve RKF. 14…”
mentioning
confidence: 99%
“…Evaluation of SGLT2is in patients with residual kidney function receiving peritoneal dialysis warrants close attention because this population may derive cardiovascular benefits and longer preservation of residual kidney function. 10 The sampling procedure and pharmacokinetic analysis also warrant consideration. A noncompartmental analysis was employed using blood samples from every 30 minutes for the first 4 hours, then at hours 24 and 48.…”
mentioning
confidence: 99%
“…Evaluation of SGLT2is in patients with residual kidney function receiving peritoneal dialysis warrants close attention because this population may derive cardiovascular benefits and longer preservation of residual kidney function. 10…”
mentioning
confidence: 99%